Pendampingan Suami pada Kunjungan ANC (Antenatal Care) berhubungan dengan Tingkat Kecemasan Ibu Hamil Trimester III - Sri Hardiani; Humaediah Lestari; Linda Lestari; Haryani Haryani (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Abstarct Introduction: husbands are expected to be involved in decision making and taking action regarding maternal health, including providing a sense of security and reducing anxiety for pregnant women with the husband's assistance. The third trimester of pregnancy is the final age of pregnancy and before delivery. Pregnancy in the third trimester is often referred to as the vigilant "waiting phase". Purpose: This study aims to determine the relationship between husband's assistance during ANC (Antenatal Care) visits and the anxiety level of pregnant women in the third trimester in the working area of ​​the Soriutu Community Health Center, Dompu Regency. Method: This research uses a descriptive correlational method, namely a correlation study with a cross sectional approach to see the relationship between husband's assistance and the level of anxiety of pregnant women. The sample used in this study was 50 third trimester pregnant women from a total population of 150 pregnant women. This data collection uses a questionnaire, using Chi-square analysis. Results: there were 27 respondents (40%) in the poor category, this can be seen from husbands who lack assistance to their wives when their wives need them, such as giving light massages when the mother feels back pain, husbands also rarely discuss future plans for the future baby. mother will be born. The statistical test results obtained P value = 0.774 < 0.05. There was no significant relationship between husband's assistance at ANC (Antenatal Care) visits and anxiety levels in third trimester pregnant women.